Retooling the ethanol industry thermophilic anaerobic digestion of thin stillage for methane production and pollution prevention - Schaefer, Scott H (Water environment research : a research publication of the Water Environment Federation, 2008)
Anaerobic digestion of corn ethanol thin stillage was tested at thermophilic temperature (55 degrees C) with two completely stirred tank reactors. The thin stillage wastestream was organically concentrated with 100 g/L total chemical oxygen demand and 60 g/L volatiles solids and a low pH of approximately 4.0. Steady-state was achieved at 30-, 20-, and 15-day hydraulic retention times (HRTs) and digester failure at a 12-day HRT. Significant reduction of volatile solids was achieved, with a maximum reduction (89.8%) at the 20-day HRT. Methane yield ranged from 0.6 to 0.7 L methane/g volatile solids removed during steady-state operation. Effluent volatile fatty acids below 200 mg/L as acetic acid were achieved at 20- and 30-day HRTs. Ultrasonic pretreatment was used for one digester, although no significant improvement was observed. Ethanol plant natural gas consumption could be reduced 43 to 59% with the methane produced, while saving an estimated $7 to $17 million ($10 million likely) for a facility producing 360 million L ethanol/y